2019
DOI: 10.32861/jssr.53.723.732
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Preventive Measures for Fibroid Among Celibate-Women in South-Western, Nigeria

Abstract: Uterine fibroid has been identified as one of the most prevailing health challenges among African women. Previous studies focused on the prevalence and prevention of fibroid among women in general, especially with regards to the biomedical science perspective. However, little attention has been given to social dimension of this medical condition particularly among Celibate-women. This study therefore investigated the prevalence and prevention of fibroid among Celibate-women, in the Catholic Ecclesiastical Prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…thus both partners are grossly involved. The husbands in the rural communities in South-western Nigeria have proven that irrespective of the power bestowed on them by their patriarchal heritage [11,30], there is still need to support their wives especially during pregnancy. This could also be because of the close family bond in the rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…thus both partners are grossly involved. The husbands in the rural communities in South-western Nigeria have proven that irrespective of the power bestowed on them by their patriarchal heritage [11,30], there is still need to support their wives especially during pregnancy. This could also be because of the close family bond in the rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…At least, one in every thirteen Nigerian woman dies during pregnancy or childbirth, and this is more prevalent in the rural population, where there are less health facilities [9,4]. More so because the decisions on the kind of health facilities to consult even during pregnancy mostly rests on the male counterparts, especially husbands [10,11] The prevailing patriarchal system in rural areas explains this. Currently, 48.8 percent of the population of Nigeria is rural (99,027,063 people in 2020), among whom about 45 per cent are women [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least, one in every thirteen Nigerian woman dies during pregnancy or childbirth, and this is more prevalent in the rural population, where there are fewer health facilities [ 3 , 8 ]. More so because the decisions on the kind of health facilities to consult even during pregnancy mostly rest on the male counterparts, especially husbands [ 9 , 10 ] The prevailing patriarchal system in rural areas explains this. Currently, 48.8% of the population of Nigeria is rural (99,027,063 people in 2020), among whom about 45% are women [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may have implications on the health-seeking behaviour of the woman, especially as husbands reserve the economic power in decisions about the healthcare of a wife. This is often prevalent in rural societies where women are predominantly economically dependent on their spouses [ 9 , 10 , 19 ]. A study conducted in Mali confirmed that men are traditionally socialized to be superior in family decision-making as they reserve the duty of providing financial support to the family [ 20 ].…”
Section: Introductionmentioning
confidence: 99%